Bromine as indicator of source of lacustrine sedimentary organic matter in paleolimnological studies. Issue 1 (1st March 2019) - Ribeiro Guevara, Sergio; Rizzo, Andrea; Daga, Romina; Williams, Natalia; Villa, Stefania
Abstract: Bromine (Br) to organic matter (OM) concentration ratio is studied in lake sediment sequences to provide information on environmental changes modifying OM production. The sequences studied were extracted from shallow lakes Morenito, El Trébol, Escondido, and Portezuelo; and deep lakes Futalaufquen, Moreno, and Traful (North Patagonia Andean range). Lake Morenito, a former Lake Moreno bay until its closure in AD 1960, showed a decrease in Br:OM ratios from 1.38 to 0.74 after lake closure, associated with an increase of primary autochthonous productivity attributable to the development of submerged and emerging macrophytes. Sedimentary sequences from Lakes Escondido, Portezuelo, and El Trébol (with large participation of macrophytes in primary productivity), and from Lakes Moreno, Futalaufquen, and Traful (with little development of littoral macrophytes), showed Br:OM ratios consistent with the Lake Morenito pattern. Consistently, the morphometric parameters mean depth and shoreline development correlate with Br:OM ratios. Therefore, Br:OM ratios can be associated with the composition of primary autochthonous productivity, with values of about 0.7 associated to significant macrophyte contributions, and higher values associated with more pelagic contributions. Accordingly, Br:OM variations along a sedimentary sequence can be associated with modifications on the composition of the primary autochthonous productivity of the water body, providing information on environmental changes.